Effectiveness of thoracic kinesio taping on respiratory function and muscle strength in patients with chronic obstructive pulmonary disease: A protocol of randomized, double-blind placebo-controlled trial. Issue 14 (9th April 2021) - Zeng, Renfeng; Tian, Ke; Xiao, Zhike
Abstract: Background: To our knowledge, only 1 study has investigated the effects of kinesio taping (KT) on pulmonary function and functional capacity of patients with chronic obstructive pulmonary disease (COPD). Therefore, there is still a lack of high-quality evidence to prove the effectiveness of KT for COPD patients. Our purpose was to investigate the effect of KT on respiratory function and muscle strength in the COPD patients who were in stable condition. Methods: This research project has been received ethical approval from the Medical Research and Ethics Committee in Affiliated Nanhua Hospital, University of South China. This work is a part of a comprehensive research project to assess and provide intervention that potentially improves respiratory function and quality of life among patients with COPD. Participants recruited into the study need to fulfill the following criteria: clinical diagnosis of COPD and symptoms indicative of exacerbation; spontaneous breathing on hospital admission; and physiotherapy since the first day of hospitalization. Patients will be assigned at random to the COPD medical treatment + KT (Group 1), or the COPD medical treatment alone (Group 2). The outcome measures are pulmonary function and respiratory muscle strength. The level of statistical significance is set as P  < .05. Results: This protocol will provide a reliable theoretical basis for the following research. Conclusions: It was hypothesized that thoracic KT could significantly change pulmonary function and functional capacity in patients with COPD. Trial registration: This study protocol was registered in Research Registry (researchregistry6632).